Head-to-head intra-individual comparison of biodistribution and tumor uptake of 68Ga-FAPI and 18F-FDG PET/CT in cancer patients - Giesel, Frederik L.; Kratochwil, Clemens; Schlittenhardt, Joel; Dendl, Katharina; Eiber, Matthias; Staudinger, Fabian; Kessler, Lukas; Fendler, Wolfgang; Lindner, Thomas; Körber, Stefan A.; Cardinale, Jens; Sennung, David; et al. (European journal of nuclear medicine and molecular imaging, 2021)
FAPI ligands (fibroblast activation protein inhibitor), a novel class of radiotracers for PET/CT imaging, demonstrated in previous studies rapid and high tumor uptake. The purpose of this study is the head-to-head intra-individual comparison of 68Ga-FAPI versus standard-of-care 18F-FDG in PET/CT in organ biodistribution and tumor uptake in patients with various cancers.
Im Titel sind die Zahlen 68 und 18 jeweils hochgestellt
Gesehen am 31.10.2023